A Branch Search Algorithm for the Knapsack Problem - Greenberg, Harold; Hegerich, Robert L. (Management Science, 1970)
This paper presents an algorithm for the solution of the knapsack problem. The method involves searching the nodes of a tree along a single branch at a time. The algorithm eliminates the computational drawbacks inherent in the usual branch and bound schemes.